VIM-1-producing Enterobacter asburiae with mobile colistin resistance genes from wastewaters - Sukkar, Iva; Valcek, Adam; Dolejska, Monika (BMC genomics, 2024)
BACKGROUND: Wastewaters are considered as important players in the spread of antimicrobial resistance, thus affecting the health of humans and animals. Here, we focused on wastewaters as a possible source of carbapenemase-producing Enterobacterales for the environment. METHODS: A total of 180 presumptive coliforms from hospital and municipal wastewaters, and a river in the Czech Republic were obtained by selective cultivation on meropenem-supplemented media and tested for presence of carbapenemase-encoding genes by PCR. Strains carrying genes of interest were characterized by testing antimicrobial susceptibility, carbapenemase production and combination of short- and long- read whole-genome sequencing. The phylogenetic tree including publicly available genomes of Enterobacter asburiae was conducted using Prokka, Roary and RAxML. RESULTS: Three VIM-producing Enterobacter asburiae isolates, members of the Enterobacter cloacae complex, were detected from hospital and municipal wastewaters, and the river. The blaVIM-1 gene was located within a class 1 integron that was carried by different F-type plasmids and one non-typeable plasmid. Furthermore, one of the isolates carried plasmid-borne colistin-resistance gene mcr-10, while in another isolate chromosomally located mcr-9 without colistin resistance phenotype was detected. In addition, the analysis of 685 publicly available E. asburiae genomes showed they frequently carry carbapenemase genes, highlighting the importance of this species in the emergence of resistance to last-line antibiotics. CONCLUSION: Our findings pointed out the important contribution of hospital and community wastewaters in transmission of multi-drug resistant pathogens.
Keywords: Environment; kolistin; mikrobiální testy citlivosti; Colistin; Wastewater; beta-laktamasy; bakteriální proteiny; Bacterial Proteins; lidé; Carbapenemase; Antimicrobial resistance; Anti-Bacterial Agents; Enterobacter; mcr; bakteriální léková rezistence; odpadní voda; beta-Lactamases; Phylogeny; Microbial Sensitivity Tests; plazmidy; Plasmids; fylogeneze; antibakteriální látky; Drug Resistance, Bacterial; Humans